Novel Heterozygous Deletion in Retinol Dehydrogenase 12 (RDH12) Causes Familial Autosomal Dominant Retinitis Pigmentosa - Sarkar, Hajrah; Dubis, Adam M.; Downes, Susan; Moosajee, Mariya (Frontiers in Genetics, 2020)
Mutations in the retinol dehydrogenase 12 (RDH12) gene are primarily associated with Leber congenital amaurosis (LCA) type 13, a severe early onset autosomal recessive retinal dystrophy. Only one family with a heterozygous variant, associated with mild retinitis pigmentosa (RP), has been reported. We report a novel heterozygous variant [(c.759del; p.(Phe254Leufs*24)], resulting in a frameshift and premature termination identified in two unrelated individuals with familial autosomal dominant RP. Both heterozygous variants are associated with a late onset RP phenotype, suggesting a possible genotype-phenotype correlation.